2016
DOI: 10.18805/ijare.v0iof.8431
|View full text |Cite
|
Sign up to set email alerts
|

Growth and instability of pineapple production in Manipur, India

Abstract: The present study was undertaken to study the trends of area, production and productivity of pineapple in Manipur. The study was based on the secondary data from 2001 to 2011. To analyze the trend of area, production and productivity of pineapple in Manipur, semi log linear functional form was used. Beside these, compound growth rate and instability index was also estimated. The effect of area, production and their interaction towards increasing production were also estimated in the present study. The instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…indicates that pineapple production has a growth rate the extent of 3.6% and it was statistically significant. The findings of the study were in line with the previous research bySingh et al (2016) who reported that the production of pineapple in Manipur has a significant positive growth rate.…”
supporting
confidence: 91%
“…indicates that pineapple production has a growth rate the extent of 3.6% and it was statistically significant. The findings of the study were in line with the previous research bySingh et al (2016) who reported that the production of pineapple in Manipur has a significant positive growth rate.…”
supporting
confidence: 91%
“…The objective of this contribution is to delineate a pineapple biorefinery that eventually adapts to the geographic and cultural conditions of a specific region of Colombia (the Choco-Colombia region), where the pineapple crop is centralized in small farms for local consumption and not in large technical conglomerates, so in many cases the production of fruits does not reach export quality (at least for fresh consumption). This situation is not only characteristic of the Choco-Colombia region, but also occurs in several areas dedicated to the cultivation of pineapples worldwide (Nanda et al, 2012;Singh et al, 2016). The differences in the expected quality of the fruit of both production schemes can be deduced from Fig 4.…”
Section: Figmentioning
confidence: 89%
“…According to Reinhardt and Rodriguez (2009), several factors must be considered when adding value to pineapples through agro industrial processing: the integration of the producer and the processing industry, the type of fruit variety compared to the application, the product portfolio, the processing technology, the logistics, marketing and longterm planning, among others. Even the socio-economic status of pineapple growers (Dickson et al, 2002;Nanda et al, 2012) as well as trends related with growth and instability of pineapple production (Singh et al, 2016) should be considered. As an example of the above, it could be obvious that for a technically grown pineapple crop with a high production volume, it can be assumed the sufficient availability of pineapple crowns to justify a sugar recovery unit such as the one included in the biorefinery scheme in Fig 2b, but for the cultivation of pineapple in small and nontechnical farms, the collection of pineapple crowns can represent economic costs that limit its viability and may be more appropriate to use the crowns as a supplement for animal feed or to obtain fibers in a small-scale production.…”
Section: Figmentioning
confidence: 99%
“…Farmers totally depended on rainfall for irrigation. The sample areas was located in the hilly region of Manipur, it was very difficult to arrange for irrigation facilities [10][11][12].…”
Section: Constraints Faced By Farmers In Pineapple Productionmentioning
confidence: 99%